SOSIALISASI PENGELOLAAN AIR BERSIH DI KAMPUNG BAINGKETE DISTRIK MAKBON - La Falihi,; Pattola, Rachmat; Beda , Mustafa Mureno Kasa; Farida, Anif (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Limited access to clean water remains a significant challenge in rural and coastal regions, including Baingkete Village, Makbon District. Local communities continue to depend on untreated natural water sources, making water quality and availability highly susceptible to environmental and seasonal variations. The objective of this community service initiative is to enhance public knowledge and awareness regarding the importance of clean water management through targeted outreach and education. The participatory approach employed includes initial observation, outreach and education, participatory discussions, and evaluation of activities. The outcomes indicate a positive response and active engagement from the community, as well as improved understanding of clean water quality and the health risks associated with using untreated water. This initiative is anticipated to promote behavioral change and reinforce sustainable, community-based clean water management.